Medicare's prospective payment system for hospitals: new evidence on transitions among health care settings - Xufeng Qian; Louise B. Russell; Elmira Valiyeva; Jane E. Miller (Rutgers University, Department of Economics, 2007)
Previous studies of Medicare's prospective payment system for hospitals (PPS), introduced in 1983, evaluated only its first few years, using data collected during the hospital stay to control for patients' health. We examine transitions among health care settings over a full decade following implementation of PPS, using survival models and a national longitudinal survey with independent information on health. We find that the rate of discharge from hospitals to nursing homes continued to rise as PPS matured, hospital readmissions from the community dropped after the early years, and risk of nursing home admission from the community soon after hospital discharge tripled. Evaluations of new payment systems for one type of provider need to be comprehensive in order to capture the full effects on other providers.
Keywords: I18; C41; 330; Medicare; prospective payment; Krankenhauskosten; Krankenversicherung; Gesundheitspolitik; USA